Pengaruh Keputusan Investasi, Keputusan Pendanaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Widi Fitri Anggreini; Muhammad Agus Salim; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study is to determine the effect of investment decisions (Price Earning Ratio), funding decisions (Debt Equity Ratio) and dividend policy (Dividend Payout Ratio) on the value of the company (Price Book Value) partially. This research sample is a manufacturing company listed on the Indonesia Stock Exchange for the period 2017-2019 using purposive sampling method, which is as many as 29 companies. The results show that: 1) There is a negative and insignificant influence of partial investment decisions (Price Earning Ratio) on the value of the company (Price Book Value) on manufacturing companies. 2) There is a positive and significant influence of partial Debt Equity Ratio on the value of the company (Price Book Value) on manufacturing companies. 3) There is a positive and significant influence of dividend policy (Dividend Payout Ratio) partially on the company's value (Price Book Value) on manufacturing companies.  Keywords: Influence of Investment Decisions (Price Earning Ratio), Debt Equity Ratio, Dividend Payout Ratio And Company Value (Price Book Value)